Cyclic AMP-dependent inotropic effects are differentially regulated by muscarinic G(i)-dependent constitutive inhibition of adenylyl cyclase in failing rat ventricle - Hussain, RI (Blackwell Publishing Ltd, 2011)
BACKGROUND AND PURPOSE: β-Adrenoceptor (β-AR)-mediated inotropic effects are attenuated and G(i) proteins are up-regulated in heart failure (HF). Muscarinic receptors constitutively inhibit cAMP formation in normal rat cardiomyocytes. We determined whether constitutive activity of muscarinic receptors to inhibit adenylyl cyclase (AC) increases in HF and if so, whether it modifies the reduced β-AR- or emergent 5-HT(4)-mediated cAMP-dependent inotropic effects. EXPERIMENTAL APPROACH: Contractility and AC activity were measured and related to each other in rat ventricle with post-infarction HF and sham-operated (Sham) controls with or without blockade of muscarinic receptors by atropine and inactivation of G(i) protein by pertussis toxin (PTX). KEY RESULTS: Isoprenaline-mediated inotropic effects were attenuated and basal, isoprenaline- and forskolin-stimulated AC activity was reduced in HF compared with Sham. Atropine or PTX pretreatment increased forskolin-stimulated AC activity in HF hearts. β-AR-stimulated AC and maximal inotropic response were unaffected by atropine in Sham and HF. In HF, the potency of serotonin (5-HT) to evoke an inotropic response was increased in the presence of atropine with no change in the maximal inotropic response. Interestingly, PTX pretreatment reduced the potency of 5-HT to evoke inotropic responses while increasing the maximal inotropic response. CONCLUSIONS AND IMPLICATIONS: Although muscarinic constitutive inhibition of AC is increased in HF, it does not contribute to the reduced β-AR-mediated inotropic effects in rat ventricle in HF. The data support the hypothesis that there are differences in the functional compartmentation of 5-HT(4) and β-AR AC signalling in myocardium during HF.